Pentecostal Entrepreneurship and Karl Marx’s Conception of Religion: Implication for Socio-Economic Development in Nigeria - Koko, John Clerk; Amadi, Emmanuel Echezolochi (NIU Journal of Social Sciences, 2026)
The role of religion in socio-economic development has often been undermined in national discussion by some who simply dismiss it as mere irrational feelings with no tangible benefits. This conception of religion is rooted in Marx’s maxim that religion is the opium of the people . On the contrary, rehabilitators of religion like Weber thinks differently insisting that socio-economic development interlaces with religious beliefs and practices. Therefore, this paper examines the role of religion in socio-economic development against the backdrop of Pentecostal entrepreneurship in Nigeria. Using the methodologies of desk research and discursive analysis, the paper argues that recent socio-economic infrastructure like hospitals, schools, restaurants, hotels, fuel stations, vocational schemes, etc. of some Pentecostal churches in Nigeria strongly subscribe to the vital role of religion in socio-economic development. In essence, religion alleviates the socio-economic status of the people than worsen it as envisaged by the denigrators of religion like Marx. Moreover, the paper concludes that rather than see religion as providing a temporary sigh of relief or escape from the hardships and injustices in society, it should be seen as playing a crucial role in socio-economic development. In this light, the paper recommends a balanced understanding of the role religion plays in human society. It also reveals how religious beliefs and practices influence economic conditions.     Keywords: Religion, Pentecostal entrepreneurship, Karl Marx, Max Weber, Socio-economic, and Nigeria